Silver-Catalyzed Decarboxylative Radical Addition/Cyclization of Oxamic Acids with Alkenes towards Quinolin-2-ones - Jin, Chengan; He, Jing-Yao; Bai, Qi-Fan; Feng, Gaofeng (Synlett, 2020)
An efficient silver-catalyzed tandem decarboxylative radical addition/cyclization of oxamic acids with alkenes has been developed. This method provides a novel and straightforward protocol toward a variety of 4-aryl-3,4-dihydroquinolin-2(1H)-ones, 4-(α-carbonyl)-3,4-dihydroquinolin-2(1H)-ones, and quinolin-2(1H)-ones in aqueous solution.
Keywords: silver catalysis; addition; cyclization; tandem reaction; oxamic acids; quinolinones